1989
DOI: 10.1128/mcb.9.1.241
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional promiscuity of the human alpha-globin gene.

Abstract: The human aL-globin gene displays the unusual property of transcriptional promiscuity: that is, it functions in the absence of an enhancer when transfected into nonerythroid cell lines. It is also unusual in that its promoter region lies in a hypomethylated HpaII tiny fragment (HTF) island containing multiple copies of the consensus sequence for the SPl-binding site. We have investigated whether there is a relationship between these two observations. First, we investigated the mouse ac-globin gene since it doe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

1990
1990
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 47 publications
2
25
0
1
Order By: Relevance
“…The response of these constructs following transfection and induction was measured by both CAT and RNA analyses (not shown). Deletion of sequences from -1375 to -76 relative to the cap site gave a decrease in the level of expression similar to that described previously (Whitelaw et al 1989), but induction remained unaffected. Removal of an additional 8 bp 3' to position -7 6 destroyed the CAAT box and caused the loss of measurable expression.…”
Section: Cis-acting Sequences Responsible For Inductionsupporting
confidence: 53%
See 1 more Smart Citation
“…The response of these constructs following transfection and induction was measured by both CAT and RNA analyses (not shown). Deletion of sequences from -1375 to -76 relative to the cap site gave a decrease in the level of expression similar to that described previously (Whitelaw et al 1989), but induction remained unaffected. Removal of an additional 8 bp 3' to position -7 6 destroyed the CAAT box and caused the loss of measurable expression.…”
Section: Cis-acting Sequences Responsible For Inductionsupporting
confidence: 53%
“…Although the ~-and [3-globin genes were both induced in transiently transfected MELCs, expression of the c~-globin gene was much greater than that of the [3-globin gene, a situation similar to that in nonerythroid cells (Banerji et al 1981;Mellon et al 1981;Humphries et al 1982;Treisman et al 1983;Whitelaw et al 1989). This suggested that the transiently transfecting globin genes gained no advantage from being expressed in an erythroid environment.…”
Section: Cell Specificity Of the Induction Responsementioning
confidence: 91%
“…pA and poly A, polyadenylation site; ex1 to ex3, exon 1 to exon 3. was found to confer a strong (ϳ30-fold) positive effect on expression, which shows that this rabbit ␣-globin 5Ј flanking DNA segment is capable of responding to an enhancer. This result is consistent with the results of earlier studies with human ␣-globin gene constructs (31,36,47). In the test shown in Fig.…”
Section: Resultssupporting
confidence: 83%
“…However, when both more extensive 5Ј flanking and internal sequences are included in the construct (e.g., ␣-Luc), inclusion of this major regulatory region has at most a two-to fourfold effect. This is comparable to the effect of the SV40 enhancer on the transient expression of an intact rabbit ␣-globin gene in K562 cells (11,22) and a human ␣-globin gene in a replicating system in HeLa cells (47). One possible explanation for this a K562 cell clones were stably transfected with human ␣-globin-luciferase fusion constructs in CpG island and non-CpG island environments.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation